SEMANTIC CHANGES IN TRANSLATION OF EUPHEMISM AND DYSPHEMISM IN TEMPO MAGAZINE - Ariani, Ni Putu; Beratha, Ni Luh Sutjiati; Malini, Ni Luh Nyoman Seri (Research And Innovation In Language Learning (RILL), 2020)
This research aims at identifying the semantic changes in the translation of euphemism and dysphemism of news text of Tempo Magazine. This research used a descriptive qualitative method and took the data from bilingual Tempo Magazine edition 2019 with Indonesian in a source language and its translation into English. The result shows that 6 types of semantic change occur in the translation of euphemism and dysphemism of Tempo Magazines such as semantic broadening, semantic narrowing, semantic metaphor, semantic pejoration, semantic amelioration, and semantic metonymy. When euphemism or dysphemism are translated into the same categories, they undergo semantic broadening, narrowing, metonymy or metaphor. While semantic change pejorations occur when euphemism is translated into dysphemism and semantic change ameliorations occur when dysphemism is translated into euphemism. Even though there are changing of the meaning from the earlier one to the new one in the translation of euphemism and dysphemism, the sense relation still tied the words up so they still have a relation between them